Pro-angiogenic effects of Guo Min decoction in a zebrafish model - Ping-Hsun Lu; Sheng-Fen Tung; Chi-Chung Wen; Ching-Yuan Huang; Jhih-Wei Huang; Chih-Hsin Chen; Yau-Hung Chen (Tzu-Chi Medical Journal)
Objectives: Guo Min decoction (GMD) is a Chinese traditional medicine that can regulate allergy-related symptoms. Although GMD treatment was reported to treat allergy-associated symptoms by regulating the immune response, the rationale between GMD treatment and angiogenesis has not been reported yet. Our objective is to investigate the angiogenesis-modulating activity of GMD. Materials and Methods: In this study, we used fluorescence recording, alkaline phosphatase (AP) activity staining, and real-time polymerase chain reaction (PCR) experiments to examine the effects of GMD on angiogenesis in a zebrafish model. Results: GMD-treated zebrafish embryos exhibited more intercapillary spaces in the caudal vein plexus (Mock: 11.1 ± 1.8 [n = 20; n: numbers of embryos]; GMD-treated: 16.2 ± 1.9 [n = 20]). AP activity staining showed that treatment with GMD and liquorice (Gan Cao, a component of GMD) induced subintestinal vein outgrowth. However, glycyrrhizin (a component of Gan Cao) had no obvious pro-angiogenic effects on zebrafish. Furthermore, real-time PCR experiments indicated that GMD exposure might be through regulating angiogenesis-related genes (cdh5, nrp1a, and flt1) expressions. Conclusion: Based on these observations, we proposed that GMD had pro-angiogenic activity in a zebrafish model, and it might partially be contributed by one of the components, liquorice.